Towards understanding global patterns of antimicrobial use and resistance in neonatal sepsis: insights from the NeoAMR network - Li, G; Bielicki, JA; Ahmed, ASMNU; Islam, MS; Berezin, EN; Gallacci, CB; Guinsburg, R; Da Silva Figueiredo, CE; Vieira, R; Silva, AR; Teixeira, C; Turner, P; et al. (BMJ Publishing Group, 2019)
Objective To gain an understanding of the variation in available resources and clinical practices between neonatal units (NNUs) in the low-income and middle-income country (LMIC) setting to inform the design of an observational study on the burden of unit-level antimicrobial resistance (AMR).